Aktivitas Antimikroba Fraksi-Fraksi Dari Ekstrak Jamur Endofit Cladosporium oxysporum Yang Diisolasi Dari Aglaia Odorata Lour - Sugijanto, Noor Erma; Dorra, Bella Lexmita (Jurnal Kedokteran Indonesia, 2012)
Background:Some endophytic fungi have shown economicpotentials for future Â production of enzyme, medicine, and biological control agent. This study aimed to examine the antimicrobial activities in ethyl acetate extract fractions of Cladosporiumoxysporumendophyticfungi against Escherichia coli, Staphylocooccusaureus,and Candida albicans. Method: CladosporiumoxysporumendophyticfungiÂ was isolated from AglaiaodorataLour (pacarCina, Java)which was collected at Purwodadi Botanical Garden, Pasuruan, East Java. C. oxysporum were cultivated, extracted and fractionated. The fractions then were applied to antimicrobial activity assay. Disc diffusion method was conducted with 2 mg/disc concentration extracts. Results: The ethyl acetate extract fractions of C.oxysporumshowed antimicrobial activities against the three microbes tested. Six of 13 fractions exhibited inhibition zone against S. aureus ATCC 6538, E. coli ATCC 8739 and C. albicans ATCC 10231. The seventh fraction exhibited the highest inhibition zone against S. aureus ATCC 6538, and C.albicans ATCC 10231. The tenth fraction exhibited the highest inhibition zone against E. coli ATCC 8739. Conclusion:Cladosporiumoxysporum from Aglaiaodoratais a good source of antimicrobial substance.The discovery of bioactive metabolites in C.oxysporumendophytic fungi allows the development of a new antimicrobial medicine for commercial use. Key words:Cladosporiumoxysporum,endophytic fungi, AglaiaodorataLour,antimicrobial activity